Calentamiento por radiofrecuencia para esterilizar pinus radiata como material para embalajes. Parte 1: Tiempo total de tratamiento - Esquivel-Reyes, Héctor; Sepúlveda-Villarroel, Víctor; Torres-Mella, José; Salvo-Sepúlveda, Linette; Salinas-Lira, Carlos; A. Ananias, Rubén (Maderas. Ciencia y Tecnología, 2018)
In this work the total heating time was studied using radio frequency to sterilize wood packaging material of Pinus radiata, through the conditions 56 ° C and 60 ° C for 30 and 1 minutes respectively, according to international phytosanitary norms. The experimental tests were carried out in a laboratory radiofrequency equipment of 3 m3 capacity. The heating time was determined and prediction models were developed, depending on the thickness, plaque separation and wood loading volume, with confidence levels above 90%. The results showed that the total time of radiofrequency sterilization was greater in the surface of the pile and were statistically similar under both treatment conditions.